Estimation of Microbial Viability Using Flow Cytometry. Issue 1 (14th April 2020) - Davey, Hazel; Guyot, Stéphane
Abstract: For microorganisms in particular, viability is a term that is difficult to define and a state consequently difficult to measure. The traditional (and gold standard) usage equates viability and culturability (i.e., the ability to multiply) but the process of determining culturability is often too slow. Flow cytometry provides the opportunity to make rapid and quantitative measurements of dye uptake in large numbers of cells and we can therefore exploit the flow cytometric approach to evaluate so‐called viability stains and to develop protocols for more routine assessments of microbial viability. This article provides a commentary and several protocols have been included to ensure that users have a firm basis for attempting these reasonably difficult assays on traditional flow cytometer instruments. What is clear is that each assay must be carefully validated with the particular microorganism of interest before being applied in any research, clinical, or service form. © 2020 The Authors.